The Comparison of One and Two Steps Equilibration in Vitrification Process on The Morphology and Viability of Mouse Blastocysts - Djuwita, Ita; Sari, Faralinda; Mohamad, Kusdiantoro (Jurnal Veteriner; Vol 11 No 3 (2010), 2010)
A study was conducted to compare the effect of one and two steps equilibration method of vitrificationon the morphology and viability of mouse blastocysts. Blastocysts were firstly exposed to modified PhosphateBuffered saline (mPBS) containing 1% Bovine Serum Albumin (BSA) proceeded by exposure in mPBSrespectively containing 0.25M sucrose (S) for 2 minutes . Blastocysts were then exposed for 2 minutesrespectively to mPS+0.5M S (one step method) or in mPBS+0.5M S+10% ethylene glycol (EG) (two stepmethod).. Blastocysts were then exposed in mPBS+0.5M S+30% EG for 60 second, loaded into 0.25 mlplastic straw, and exposed immediately in vapor of liquid nitrogen for 10 second before they were and thenplunged into liquid nitrogen. The blastocysts were reconstituted by diluting with mPBS+0.5M S followedby mPBS+0.25M S for each 3 min and washed in mPBS without sucrose. The viability of cells was assessedby fluorescent vital staining, by re-expansion for 24 hours in vitro culture, and by implantation into therecipient oviduct. The percentages of morphologically normal blastocysts following recovery fromvitrification were higher (p<0.05) in one step equilibration than in those of two steps methods (89.6%. vs82.6%). The viability of blastocysts examined under light microscope after staining with biz-benzimidizepropidiumiodine and 24 hours in vitro culture in one step methods (64.0%; 57.8%) were higher (p<0.05)compared with two steps methods (40.0%; 35.6%), respectively. The implantation rate of vitrifiedblastocysts (23.1%) was not significantly different to that of fresh blastocysts (33.4%). These resultsshowed that the one and two step equilibration methods are effective for vitrification and maintaining theviability of the mouse blastocysts.
Keywords: Morphology, viability, vitrification, blastocysts, mouse